Preparation of New Chiral Building Blocks by a Mukaiyama–Michael Reaction of 2-(Phenylsulfonyl)cyclopent-2-en-1-one - Sugiyama, Ryoji; Nakada, Masahisa (Synlett, 2023)
A highly enantio- and diastereoselective Mukaiyama–Michael reaction of 2-(phenylsulfonyl)cyclopent-2-en-1-one by using an enol silane of tert-butyl thiopropionate is described. The product was formed in 87% yield with a dr of 27:1 and 91% ee under stoichiometric conditions, whereas the yield, dr, and ee were 89%, 49:1, and 88% ee, respectively, under catalytic conditions. A highly stereoselective epimerization of the product of the Mukaiyama–Michael reaction which proceeds in 77% yield with a dr of 22:1 is also described. Because both enantiomers of the ligand for this Mukaiyama–Michael reaction are available, a method for the synthesis of all four stereoisomers of the product as useful chiral building blocks has been established.
Keywords: Mukaiyama–Michael reaction; asymmetric catalysis; enantioselectivity; diastereoselectivity; chiral building blocks; phenylsulfones